Warfarin Dosing in Patients With Impaired Kidney Function - Limdi, Nita A (2010)
BACKGROUND: Warfarin, a drug primarily metabolized by the cytochrome P450 system, is initiated at similar doses and managed similarly in patients with kidney impairment as in the general medical population. Unfortunately, few data exist to guide dose adjustment in patients with reduced kidney function. Herein we determine the degree of warfarin dose reduction associated with kidney impairment and make recommendations for warfarin dosing. STUDY DESIGN: Cross-sectional analysis. SETTING & PARTICIPANTS: Chronic warfarin users followed at anticoagulation clinics (n=980); 708 participants from the University of Alabama (UAB) and 272 participants from the University of Chicago (UIC). PREDICTOR: No/mild (eGFR≥60ml/min/1.73 m(2)), moderate (eGFR=30–59ml/min/1.73 m(2)) and severe (eGFR<30ml/min/1.73 m(2)) kidney impairment, CYP2C9 and VKORC1 genotype, age, race, gender, body mass, socio-demographic factors, smoking status, alcohol, vitamin K intake, comorbid conditions (e.g. CHF, etc.) and drug interactions (e.g. amiodarone, statins, etc.). OUTCOME & MEASUREMENT: Warfarin dose (mg/day) was evaluated using linear regression after adjustment for clinical demographic and genetic factors. RESULTS: The prevalence of moderate kidney impairment (31.8% and 27.6%) and severe kidney impairment (8.9% and 6.6%) was similar in the UAB and UIC cohorts. Warfarin dose requirements were significantly lower in patients with moderate and severe kidney impairment compared to those with none/mild kidney impairment in the UAB (p<0.001) and UIC (p<0.001) cohorts. Compared to patients with no/mild kidney impairment, patients with moderate kidney impairment required 9.5% lower doses (p<0.001) and patients with severe kidney impairment required 19% lower doses (p<0.001). LIMITATIONS: No measurement of warfarin, serum albumin, vitamin K and clotting factor levels, no evaluation of other markers (e.g. cystatin). CONCLUSION: Moderate and severe kidney impairment were associated with a reduction in warfarin dose requirements.